The Difference in the Changes of Indoxyl Sulfate after Catheter Ablation among Atrial Fibrillation Patients with and without Kidney Dysfunction - Koike, Hideki (Sci Rep, 2020)
Indoxyl sulfate (IS), a protein-bound uremic toxin, induces chronic kidney disease (CKD) and atrial fibrillation (AF). Catheter ablation (CA) of AF improves the renal function. However, the transition of uremic toxins is unclear. This study aimed to investigate the transition of the serum IS level in AF patients with and without CKD after CA. A total of 138 consecutive AF patients who underwent CA and maintained sinus rhythm were prospectively enrolled (paroxysmal AF 67.4%). The patients were divided into 4 groups (non-CKD/low-IS:68, non-CKD/high-IS:28, CKD/low-IS:13, and CKD/high-IS:29). The plasma IS levels and estimated glomerular filtration rate (eGFR) were determined before and 1-year after CA. CKD was defined as CKD stage III and a high-IS according to the mean IS (IS ≥ 1.1 μg/ml). CA significantly improved the eGFR in CKD patients (p < 0.001). The serum IS level in the non-CKD/high-IS group was significantly decreased (from 1.7 ± 0.7 to 1.1 ± 0.6 μg/ml, p < 0.001). However, the serum IS level in the CKD/high-IS group did not improve (from 1.9 ± 0.9 to 1.7 ± 0.7 μg/ml, p = 0.22). The change in the IS in the CKD patients significantly differed from that in those without CKD. In the CKD patients, CA did not significantly decrease the IS, a risk factor of CKD, regardless of an improved eGFR.